The Effect of Price Earning Ratio (PER), Debt To Equity Ratio (DER) and Return on Asset (ROA) on Stock Prices in PT Sekar Laut Tbk. - safitri, nurayu; Pratiwi, Aliah (INVOICE : JURNAL ILMU AKUNTANSI, 2022)
This study aims to examine the effect of Price Erning Ratio (PER), Debt To Equity Ratio (DER) and Return On This study aims to determine the effect of Price-to-Earnings Ratio (PER), Debt-to-Equity Ratio (DER) and Return on Assets (ROA) on the stock price of PT Sekar Laut Tbk. The research instrument used is a list of tables, namely the financial statements of PT Sekar Laut Tbk and a list of 10-year stock prices from 2011 to 2020. The research sample used is data from the 10-year financial statements of PT Sekar Laut Tbk from 2011 to 2020. While the sampling technique used is purposive sampling, the criteria are based on the availability of the latest data and research variable data to be used. The data in this study were processed using SPSS. The hypothesis testing method uses a significance level of 5%. The results show that the Price Earning Ratio (PER) has a significant effect on stock prices, the debt-equity ratio (DER) has no significant effect on stock prices and return on assets (ROA) has a significant effect on stock prices, significant effect.Keywords: Price Earning Ratio (PER), Debt To Equity Ratio (DER), Return On Assets (ROA), and Stock Prices.